Crimination of Acts of Violence Which Performed Arbitrarily for Superiors Against Underboards in the Military Environment - Anggriani Wau (LEGAL BRIEF, 2023)
This research aims to investigate the process of prosecution for arbitrary acts of violence committed by superiors against subordinates in the military environment. The study will employ a qualitative approach by collecting data through interviews with key informants who have experiences in the military environment, such as military legal experts, military personnel, and victims of violent acts. Data will also be gathered through a literature review on military policies and laws related to cases of violence by superiors against subordinates.The findings of this research will provide a clear overview of the prosecution process for acts of violence in the military environment and identify the factors that influence the success or failure of such processes. This study will also provide policy recommendations to enhance the effectiveness of prosecuting acts of violence by superiors in the military environment and pave the way for further research on human rights issues in the military context